2023
DOI: 10.3389/fonc.2022.1093496
|View full text |Cite
|
Sign up to set email alerts
|

The (Sialyl) Tn antigen: Contributions to immunosuppression in gastrointestinal cancers

Abstract: Cellular signaling pathways are intricately regulated to maintain homeostasis. During cancer progression, these mechanisms are manipulated to become harmful. O-glycosylation, a crucial post-translational modification, is one such pathway that can lead to multiple isoforms of glycoproteins. The Tn (GalNAc-O-Ser/Thr) and Sialyl Tn (STn; Neu5Ac-GalNAc-O-Ser/Thr) antigens resulting from the incomplete synthesis of fully branched O-glycan chains on proteins contribute to disease progression in the pancreas and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…As glycans have evolved into essential components within homeostatic circuits, functioning as precise modulators of immunological responses, they emerge as potential molecular targets for intentionally modulating immune tolerance and activation across a spectrum of pathological scenarios. The recent review article emphasizes the significant role of Tn and STn antigen expression in gastrointestinal tumors in contributing to immunosuppression [49]. The focal point remains on innate immune system cells, specifically those expressing glycan-binding receptors like CD301 (MGL) [50], Siglec-4, -5, -14, and -15 [51], and potentially other receptors selectively interacting with tumor O-glycans.…”
Section: Discussionmentioning
confidence: 99%
“…As glycans have evolved into essential components within homeostatic circuits, functioning as precise modulators of immunological responses, they emerge as potential molecular targets for intentionally modulating immune tolerance and activation across a spectrum of pathological scenarios. The recent review article emphasizes the significant role of Tn and STn antigen expression in gastrointestinal tumors in contributing to immunosuppression [49]. The focal point remains on innate immune system cells, specifically those expressing glycan-binding receptors like CD301 (MGL) [50], Siglec-4, -5, -14, and -15 [51], and potentially other receptors selectively interacting with tumor O-glycans.…”
Section: Discussionmentioning
confidence: 99%
“…This connection implies that the appearance of Tn and sTn within cells could be one of the initial steps in the development of colorectal cancer ( 34 ). Moreover, the neo- or over-expression of Tn, sTn, and T antigens is not limited to colorectal cancer but occurs in many types of cancer, including gastric, colon, breast, lung, esophageal, prostate, and endometrial cancer ( 60 , 61 ). This widespread occurrence underscores the significance of these antigens in cancer biology, particularly in promoting tumor metastasis.…”
Section: C1galt1 In Colorectal Cancermentioning
confidence: 99%
“…ST6GalNAc I, which adds Neu5Ac to O-linked GalNAc residues to form sialyl-Tn (STn), is particularly significant [ 76 ]. Evidence suggests that the overexpression of STn is associated with poor clinical prognosis in a wide range of cancer types [ 27 , 77 ], making it a well-known tumor-associated carbohydrate antigen. One functional study found that ST6GalNAc I can promote tumor growth and metastasis and is related to cancer cell stemness [ 78 ].…”
Section: Sialylation Accumulates In Cancer Tissues and Promotes Tumor...mentioning
confidence: 99%